The Fatty Acid Composition and Properties of Oil Extracted from Fresh Rhizomes of Turmeric (Curcuma longa Linn.) Cultivars of Bangladesh - Paul, BK; Munshi, MMU; Ahmed, MN; Saha, GC; Roy, SK (Bangladesh Journal of Scientific and Industrial Research, 2011)
The fresh rhizomes of Curcuma longa Linn. (Turmeric or Holud) collected from three different places of Bangladesh were investigated to extract oil, its fatty acid composition and its physico-chemical properties. The rhizomes contained 8.76 - 10.92% oil. The percentage compositions of fatty acids were identified and quantified by GLC. The saturated and unsaturated fatty acid contents of three places were found to vary within 22.25 - 23.44% and 76.11 - 77.59%, respectively. Among identified six fatty acids, oleic acid contributed the highest proportion (56.24 - 58.88%), followed by myristic acid (16.25 - 17.71%); whilst, palmitic (5.59 - 6.00%), linoleic (10.90 - 12.82%), linolenic (4.15 - 5.46%) and ecosenoic acid (2.72 - 3.25%) together contributed the rest. Physico - chemical properties of the extracted oil were also investigated. The specific gravity, refractive index, optical rotation were recorded as 0.892 to 0.919 at 30°C, 1.431 to 1.465 at 30°C and +11.54° to +13.56° at 26°C, respectively. The chemical properties like saponification value (195.23 - 205.33), iodine value (75.53 - 90.47), peroxide value (23.25 - 36.16), acid value (11.08 - 11.32), ester value (56.30 - 64.13) and percentage of unsaponifiable matter (8.31 - 15.04%) were determined. Overall fresh Turmeric oil can be considered as a good source of oleic acid. Keywords: Curcuma longa; Fresh turmeric oil; Fatty acid composition; Oleic acid; Gas liquid chromatography. DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8116 Bangladesh J. Sci. Ind. Res. 46(1), 127-132, 2011